Putting the organic label in context: Examining the interactions between the organic label, product type, and retail outlet. (April 2016) - Ellison, Brenna; Duff, Brittany R.L.; Wang, Zongyuan; White, Tiffany Barnett
Highlights: Few studies consider the context in which organic purchases take place. We study how the organic label interacts with the product type and retail contexts. Further, we examine how these interactions impact downstream product evaluations. We find organic labeling benefits virtue and vice products in distinct aspects. Retailers are a crucial factor that moderates the evaluation of organic products. Abstract: The organic label has been studied extensively in the literature; however, few studies take into consideration the context in which the organic purchase takes place. In this study, we examine the product type (virtue vs. vice) as well as the purchase context (retailer: Target vs. Walmart). Using an online experiment with U.S. consumers ( N  = 605), we determine how the organic label interacts with each of these contexts and how these interactions impact downstream evaluations such as expected taste, nutrition, safety, likelihood of purchase, and attitude and trust toward the product's brand. Results of the study reveal both the organic label and retail context impact product evaluations. First, results showed organic products were perceived more favorably on a number of measures (including nutrition, safety, brand attitude, and brand trust) than their non-organic counterparts, providing evidence of an organic "halo" effect. Interestingly, though, the organic "halo" did not extend to two measures: expected taste and likelihood of purchase. Secondly, organic labeling benefits virtue and vice products in distinct aspects – the organic virtue product had better expected taste while the organic vice product had higher expected nutrition. Finally, we find that retailers are a crucial factor that moderates the evaluation of organic products. Our results suggest retailers like Target may be better outlets for promoting organic vice products whereas retailers like Walmart may only be good outlets for promoting organic virtue products. This study has important implications for the National Organic Program, the Organic Trade Association, producers, and food brand managers.